Surveillance pouchoscopy for dysplasia: Cleveland Clinic Ileoanal Pouch Anastomosis Database. Issue 13 (20th July 2020) - Lightner, A L; Vaidya, P; Vogler, S; McMichael, J; Jia, X; Regueiro, M; Qazi, T; Steele, S R; Church, J
Abstract: Background: No formal guidelines exist for surveillance pouchoscopy following ileal pouch–anal anastomosis (IPAA) for ulcerative colitis. Methods: All adults who had previously had IPAA for ulcerative colitis, and underwent a pouchoscopy between 1 January 2010 and 1 January 2020, were included. Results: A total of 9398 pouchoscopy procedures were performed in 3672 patients. The majority of the examinations were diagnostic (8082, 86·0 per cent; 3260 patients) and the remainder were for routine surveillance (1316, 14·0 per cent; 412 patients). Thirteen patients (0·14 per cent of procedures) were found to have biopsy-proven neoplasia at the time of pouchoscopy; seven had low-grade dysplasia (LGD) (0·07 per cent; all located in the anal transition zone), none had high-grade dysplasia (HGD) and six (0·06 per cent) had invasive adenocarcinoma (4 in anal transition zone and 6 in pouch). Of the six patients with adenocarcinoma, four had neoplasia at the time of proctocolectomy (2 adenocarcinoma, 1 LGD, 1 HGD); all six were symptomatic with anal bleeding or pelvic pain at the time of pouchoscopy, had a negative surveillance pouchoscopy examination within 2 years of diagnosis of adenocarcinoma, had palpable masses on digital rectal examination, and had visible lesions at the time of pouchoscopy. Conclusion: Surveillance pouchoscopy is not recommended in asymptomatic patients because significant neoplasia following IPAA for ulcerative colitis is rare. Graphical Abstract: Pouchoscopy has long been used as a surveillance tool for pouch neoplasia after ileal pouch–anal anastomosis (IPAA). The rate of neoplasia remains largely unknown. In this study, the highest risk was in patients with cancer in the anal transition zone at the time of IPAA. Not needed routinely